Paleomagnetism of Holocene lava flows from the Reykjanes Peninsula and the Tungnaá lava sequence (Iceland): implications for flow correlation and ages (Dataset) ... - Pinton, Annamaria; Giordano, Guido; Speranza, Fabio; Þórðarson, Þorvaldur (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Paleomagnetism of Holocene lava flows from the Reykjanes Peninsula and the Tungnaá lava sequence (Iceland): implications for flow correlation and ages ...